Reflections of Self: How Social Media Shapes Teen Body Image - Syaifussalam, M. Lathief; Intansari, Fixi; Hanifah, Raidah; Larasati, Bayu Sekar; Wigati, Meilia; Wilantika, Rima (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research explores how advances in information technology, particularly through social media, have transformed communication patterns and influenced teenagers' body image perceptions. Employing a qualitative approach, the study conducted in-depth interviews with three teenage girls aged 17-21 who are active on social media. The findings indicate that many participants experience dissatisfaction with their bodies due to comparisons with prevalent beauty standards. This aligns with social comparison theory, which suggests that individuals often evaluate their appearance by contrasting themselves with others. Social interactions on social media, including comments and likes, also play a significant role in shaping self-confidence. While the pressure to conform to unrealistic beauty ideals is a notable negative effect, some participants reported feeling motivated to pursue healthier lifestyles as a positive outcome. The study highlights the need for effective interventions aimed at educating adolescents about healthy social media use and raising awareness of its potential effects on body image.